Evaluation of skin expression profiles of patients with vitiligo treated with narrow-band UVB therapy by targeted RNA-seq - Ocampo Candiani, Jorge; Salinas Santander, Mauricio Andrés; Treviño Alvarado, Víctor Manuel; Ortiz López, Rocío; Ocampo Garza, Jorge; Sánchez Domínguez, Celia Nohemí (Sociedade Brasileira de Dermatologia e Sifilografia, 2018)
Abstract: Background: Vitiligo is characterized by a lack of pigmentation in the skin. To date, there are no studies that analyze the changes in gene expression in the skin of vitiligo patients in response to narrow-band ultraviolet B (nb-UVB) phototherapy treatment. oBjective: Explore the usefulness of new generation RNA sequencing in the identification of gene expression changes in the skin of vitiligo patients treated with nb-UVB phototherapy. Methods: Four skin biopsies (4mm in diameter) were collected from 45 Mexican vitiligo vulgaris patients, 2 specimens before and 2 after treatment with nb-UVB phototherapy, obtained from pigmented and non-pigmented tissue. RNA extracted from the biopsies was analyzed using the Illumina TruSeq Targeted RNA Expression protocol to study the expression of genes that participate in pathways of skin homeostasis. The 2 groups were compared using Student’s t-test and the Mann-Whitney U-test. results: The expression analysis identified differences in 12 genes included in this study after comparing the samples obtained before and after treatment: 5 genes involved in skin pigmentation, 2 genes involved in apoptosis, 2 genes involved in cell survival, 2 genes involved in oxidative stress responses and 1 gene involved in signal transduction mechanisms (p<0.05). study liMitations: The small size of skin biopsies limits the amount of RNA obtained, the number of genes to be analyzed and the use of conventional techniques such as RT-qPCR. conclusion: We demonstrated usefulness of new generation RNA sequencing in the identification of gene expression changes, in addition to identifying new targets in the study of vitiligo.